Political Theology on Edge : Ruptures of Justice and Belief in the Anthropocene - Keller, Catherine, 1953-; Crockett, Clayton, 1969- (Book collections on Project MUSE., 2022)
"In Political Theology on Edge, the discourse of political theology is seen as situated on an edge-that is, on the edge of a world that is grappling with global warming, a brutal form of neoliberal capitalism, protests against racism and police brutality, and the COVID-19 pandemic. This edge is also a form of eschatology that forces us to imagine new ways of being religious and political in our cohabitation of a fragile and shared planet. Each of the essays in this volume attends to how climate change and our ecological crises intersect and interact with more traditional themes of political theology. While the tradition of political theology is often associated with philosophical responses to the work of Carl Schmitt-and the critical attempts to disengage religion from his rightwing politics-the contributors to this volume are informed by Schmitt but not limited to his perspectives. They engage and transform political theology from the standpoint of climate change, the politics of race, and non-Christian political theologies including Islam and Sikhism. Important themes include the Anthropocene, ecology, capitalism, sovereignty, Black Lives Matter, affect theory, continental philosophy, destruction, and suicide. This book features world renowned scholars and emerging voices that together open up the tradition of political theology to new ideas and new ways of thinking. Contributors: Gil Anidjar, Balbinder Singh Bhogal, J. Kameron Carter, William E. Connolly, Kelly Brown Douglas, Seth Gaiters, Lisa Gasson-Gardner, Winfred Goodwin, Lawrence Hillis, Mehmet Karabela, Michael Northcott, Austin Roberts, Noëlle Vahanian, Larry L. Welborn"--